Exploration of the Molecular Mechanism for Lipoprotein Lipase Expression Variations in SH-SY5Y Cells Exposed to Different Doses of Amyloid-Beta Protein - Zhang, Jingzhu; Liu, Yufan; Wang, Sihui; Que, Ran; Zhao, Weidong; An, Li (Frontiers in Aging Neuroscience, 2020)
Progressive accumulation of amyloid-beta (Aβ) plaques in brain is a characteristic pathological change in Alzheimer’s disease. We previously found the expression of LPL was increased in SH-SY5Y cells exposed to low-dose Aβ and decreased in cells with high-dose Aβ exposure, but the molecular mechanism is still unclear. On the basis of previous studies, the opposite regulation of histone deacetylase2 (HDAC2) and HDAC3 on LPL expression probably explain the above molecular mechanism, in which microRNA-29a and peroxisome proliferator-activated receptor γ (PPARγ) may be involved. This study further revealed the mechanism of HDAC2 and HDAC3 on conversely regulating LPL expression. The results showed that HDAC2 down-regulated microRNA-29a by decreasing histone acetylation (Ace-H3K9) level in its promoter region, subsequently increasing LPL expression directly or through PPARγ/LPL pathway; HDAC3 decreased LPL expression through inhibiting Ace-H3K9 levels in LPL and PPARγ promoter regions and up-regulating microRNA-29a. This study also found that with increasing concentrations of Aβ in cells, HDAC2 and HDAC3 expression were gradually increased, and Ace-H3K9 levels in LPL and PPARγ promoter region regulated by HDAC3 were decreased correspondingly, while Ace-H3K9 levels in microRNA-29a promoter region modulated by HDAC2 were not decreased gradually but presented a U-shaped trend. These may lead to the results that a U-shaped alteration in microRNA-29a expression, subsequently leading to an inverse U-shaped alteration in PPARγ or LPL expression. In conclusion, HDAC2 and HDAC3 at least partly mediate LPL expression variations in different concentrations of Aβ exposed SH-SY5Y cells, in which microRNA-29a and PPARγ are involved, and the histone acetylation level in microRNA-29a promoter region plays a key role.